2020
DOI: 10.1038/s41598-020-71792-3
|View full text |Cite
|
Sign up to set email alerts
|

APRIL-producing eosinophils are involved in gastric MALT lymphomagenesis induced by Helicobacter sp infection

Abstract: The roles of the inflammatory response and production of a proliferation-inducing ligand (APRIL) cytokine in gastric mucosa-associated lymphoid tissue (MALT) lymphomagenesis induced by Helicobacter species infection are not clearly understood. We characterized the gastric mucosal inflammatory response associated with gastric MALT lymphoma (GML) and identified APRIL-producing cells in two model systems: an APRIL transgenic mouse model of GML induced by Helicobacter infection (Tg-hAPRIL) and human gastric biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“… 10 This link is most clearly established for Helicobacter pylori and gastric MALT lymphoma. 32 , 33 , 34 The importance of this stimulation in vivo has been clearly demonstrated by the induction of remissions in gastric MALT lymphomas with antibiotic treatment to eradicate Helicobacter pylori. 35 , 36 A role for antigenic stimulation by Chlamydia psittaci and Borrelia burgdorferi has been proposed for some cases of ocular adnexal and cutaneous MALT lymphomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 This link is most clearly established for Helicobacter pylori and gastric MALT lymphoma. 32 , 33 , 34 The importance of this stimulation in vivo has been clearly demonstrated by the induction of remissions in gastric MALT lymphomas with antibiotic treatment to eradicate Helicobacter pylori. 35 , 36 A role for antigenic stimulation by Chlamydia psittaci and Borrelia burgdorferi has been proposed for some cases of ocular adnexal and cutaneous MALT lymphomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 39 , 40 The eradication of Helicobacter pylori associated with gastric or Chlamydia psittaci causing ocular adnexa MALT lymphoma by antibiotic therapy led to protracted remissions. 10 , 32 , 34 , 39 , 41 Thus, successful eradication or removal of suspected trigger factors, for example, smoking, should be of utmost priority.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic H. pylori infection induces the secretion of pro-inflammatory cytokines by macrophages and dendritic cells, such as interleukin-1 beta (IL-1β), TNF-α, IL-8 and IL-6, and allows differentiation of Th1 and Th17 cells, which are involved in establishing persistent inflammation [ 38 ]. In gastric MALT-lymphoma, H. pylori -induced antigenic stimulation results in the formation of T-cell infiltrates that invade and destroy gastric glands [ 39 ]. These reactive Th1 CD4 + lymphocytes produce high levels of IFN-γ, and facilitate the proliferation of neoplastic B cells through CD40L-CD40 co-stimulation, and the secretion of Th2 cytokines including IL-4 [ 40 ].…”
Section: Role Of Bacteria In Gastrointestinal Lymphomamentioning
confidence: 99%
“…Recent findings indicated that a proliferation-inducing ligand (APRIL) expressed by neutrophils, eosinophils and tumor-infiltrating macrophages seems to be important for gastric lymphogenesis induced by H. pylori [ 42 ]. Recently, Blosse et al characterized the inflammatory response associated with gastric MALT lymphoma in the stomach of transgenic C57BL/6 mice, and additionally found APRIL-producing eosinophilic polynuclear cells in the lymphoid infiltrates of patients with gastric MALT lymphoma [ 39 ]. The authors have demonstrated that the T reg -balanced inflammatory environment is an important contributor to gastric lymphogenesis [ 39 ].…”
Section: Role Of Bacteria In Gastrointestinal Lymphomamentioning
confidence: 99%
See 1 more Smart Citation